Does Instructional Quality Impact Male and Female University Students Differently? Focusing on Academic Stress, Academic Satisfaction, and Mental Health Impairment - Rubach, Charlott; von Keyserlingk, Luise; Simpkins, Sandra D.; Eccles, Jacquelynne S. (Frontiers in Education, 2022)
Gender differences in university students’ well-being and mental health are prominent concerns in higher education. In COVID-19, male and female students reported specific stressors that impacted their well-being and mental health, including difficulty concentrating, concerns about academic performance, and workload in the classroom. All of these stressors could be addressed by instructional quality in courses. The following study seeks to understand better the associations between instructional quality and mental health impairment of male and female undergraduate students during the COVID-19 pandemic. We asked if experienced instructional quality has a protective effect on students’ mental health impairment through academic stress and satisfaction across gender. We used longitudinal data from an ethnically diverse sample of 209 students (68% females, 82% freshmen, 50% Asian, 32% Hispanic, 13% White, 5% other) from a public university in California, United States. Data were assessed during the academic Winter and Spring quarters of 2020, i.e., before and after the onset of the COVID-19 pandemic in the U.S. Associations between instructional quality and students’ mental health impairment did not differ across gender. Findings indicated that instructional quality experienced at the beginning of the Spring quarter 2020 was indirectly related to male and female students’ mental health impairment at the end of this quarter. The association was mediated by academic satisfaction. That indicated a protective effect of instructional quality on students’ mental health impairment. However, no effect on the change of mental health was found. Gender differences occurred in the link between academic stress and mental health impairment. Academic stress was a stronger predictor of mental health impairment for female students compared to male students. Furthermore, only for female students, academic stress impacts changes in mental health impairment. We discuss practical implications for higher education. First, our study highlighted that instructional quality in higher education courses might lead to satisfaction and help protect students’ mental health in university. Second, higher education might consider providing additional support for female students to improve their stress management. We argue that improving and enhancing the academic environment is relevant rather than reducing the burden of stressors.